Understanding and Building on Indigenous Agro-Pastoral Adaptation strategies for Climate Change in Sub-Saharan Africa: Experiences from Rural Cameroon (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Rural communities in the Sub-Sahara African region have become focal points for climate adaptation especially in the agricultural sector. This is due to their significant involvement in agro-pastoral activities which constitute the lifeblood of most of the economies of this region, with about 85% of the indigenous populations relying on it for their survival. Both long and short term climatic oscillations have succeeded, and will continue to disrupt crop and livestock output thus signaling threats to food security. Although the communities have either consciously or unconsciously made use of some indigenous adaptation strategies, they are judged to be weak at the moment. This requires the designation of context-specific agro-pastoral adaptation frameworks. Using focus group discussions (FGDs) of 6 agro-pastoral groups (10 representatives each) in this region, complemented by content analysis, field surveys and the extensive review of literature on case studies for other SSA communities, we analyze current indigenous adaptation mechanisms in the agro-pastoral sector and attempt to construct an indigenous adaptation framework for rural agro-pastoral communities in Cameroon. Our analysis of data leads us to conclude that current adaptation measures rely mainly on crop diversification and mixed farming. Although these methods are good, the scale of operation and the degree of diversification is still low to climate-proof the agro-pastoral sector. Furthermore, these changes are introduced in the midst of poor farming practices such as slash and burn and related systems. Current indigenous adaptation strategies are weak and are correlated with income levels, level of farmers involvement in organizations, knowledge and perception. We recommend the effective engagement of agro-pastoral stakeholders as key in developing an adaptable framework, based on their knowledge of current adaptation strategies.